ROLE OF YOGA IN MANAGEMENT OF LOW BACK PAIN - Kumar Sunil (International Journal of Applied Ayurved Research, 2016)
Back pain is the leading cause of occupational disability in the world and the most common cause of missed workdays. As the population advances our lives become more sedentary, stressful, and less time to relax the body posture this situation is unlikely to change low back pain. If these back pains persist more than three month become chronic. Today so many approaches present for low back pain but it is not relief completely. Therefore, it is essential to think about alternative approaches for low back pain management. Yogic practices are best modalities for management of low back pain which not only relief the pain but also release the stress. Yoga is an applied science of life, working on all aspects of individual like physical, mental, intellectual, emotional and spiritual, so that Yogic approach is most beneficial for many peoples.